Organização espaço temporal do rolamento para frente - Alaercio Perotti Júnior; Ana Maria Pellegrini (Universidade Federal do Rio Grande do Sul, 2001)
This study focus on the forward roll taking into account the environmental constraints due the surface (mattress and tatame) and intrinsic constraints imposed by growth and development. Phase portraits of body segments obtained from angular displacement and velocity were employed for ihe analysis ofthe spatial-temporal organization of the performance. The trajectories ofthe orbits of of the leg and trunk segments showed to be different among themselves but similar between subjects, mdependently of chronological age and surface used. Less variability in phase portraits of body segments was observed in adults as compared with the younger age groups.